The effect of weight change over a 2-year period on inflammatory status in postmenopausal women. Issue 3 (March 2018) - Cronin, Barbara; Allsopp, Philip; Slevin, Mary; Magee, Pamela; McCaffrey, Tracy; Livingstone, M.; Strain, J. J.; McSorley, Emeir
Abstract Background/objectives Body fat distribution has been shown to be a predictor of adhesion molecule and inflammatory marker expression albeit the effect of modest weight change on concentrations of adhesion molecules and inflammatory markers in postmenopausal women are not fully understood. The primary aim was to investigate the effects of weight change on adhesion molecules and inflammatory markers over 24 months in postmenopausal women. Subjects/methods Body composition was assessed in 254 healthy postmenopausal women using dual-energy X-ray absorptiometry (DXA). Adhesion molecules and inflammatory markers were analysed by multiplex ELISA. Participants weight gain/loss at 24 months was defined as any value that was either above/below the weight value recorded at baseline. Results Postmenopausal women with an average weight loss of 3% had significantly decreased leptin concentrations by 18% at 24 months (P < 0.01). A 4% increase in body weight or a 9% increase in FMI significantly increased intercellular adhesion molecule-1 (ICAM-1), tumour necrosis factor-α (TNF-α) and leptin concentrations in postmenopausal women at 24 months (P < 0.01). Conclusions Modest weight loss in postmenopausal women has a lowering effect on leptin concentrations over 24 months which may improve inflammatory status whilst modest weight gain increases ICAM-1, leptin and TNF-α, markers which are associated with a pro-inflammatory state and vascular complications.